Determination of Heavy Metals in Imported Canned Fish that Sold in Baghdad Markets - Al-Azzawi, Mohammed; Al-Ani, Liqaa (Iraqi Journal of Science, 2023)
The concentrations of Pb, Zn, Hg and Cu were determined in twenty sample of canned fish, samples were collected with different origin with two meals from local markets at Baghdad city for the period (October 2012-February 2013),results of study were appeared variation in mercury concentration of canned fish between November and February .The highest concentration of mercury (0.1 mg/kg) was observed in “Hawesta” brand and “Ocean wave” ” brand , the lowest average concentration for mercury 0.01ppm in “Habar”,”Durra” and ”Sayad” brand during( Nov.2012-Feb.2013 ) and have not recorded any concentration for mercury in “Yasmine” brand during (Nov. 2012-Feb. 2013).The maximum level of zinc reached in November. rather than in Febreuary ,Zn concentration varied from (6.46-18.6 mg/kg ) and the lowest concentration of Zn in canned fish from (0.010 - 0.370mg/kg). The results findings acceptable limit with Iraq standard.In this study we showed the concentration of copper varied from (0.073-10.216 mg/kg) .The highest concentration of copper (10.216mg/kg) was observed in “Habar” brand the lowest concentration of copper (0.073mg/kg) was observed in “Durra” brand , “Founty”and”Herring fillets” were recorded 0.19 mg/kg and 0.16 mg/kg.